Relation between sensory analysis and rheology of body lotions. (5th April 2016) - Moravkova, T.; Filip, P.
Abstract: Objective: Evaluation of sensory attributes of cosmetic products is traditionally based on sensory panels. However, in some cases, a suitable candidate method that can reduce time and costs is the use of instrumental analysis that can detect relatively very small changes of entry ingredients. Such approach has been already applied for emollients, salt content, stabilizers, etc. The aim of this contribution is to apply the relations between sensory analysis and rheology to a series of body lotions differing in the contents of emulsifiers and viscosity regulators. Methods: Sensory and rheological analyses are related. Rheological analysis can represent a good alternative to basic orientation in chosen customer's feelings. A rotational rheometer is the only instrumental device required for the measurements. Results: An empirical rheological model was proposed by means of which the selected sensory attributes were evaluated using the numerical values of adjustable model parameters. This approach exhibited a very good agreement with the results obtained by the sensory panel. Conclusion: It was shown that a description of chosen sensory attributes can be responsibly carried out by rheological measurements, that is through the attained numerical values of the parameters appearing in a proposed empirical model characterizing shear viscosity of body lotions. Abstract : An empirical rheological model was proposed by means of which the selected sensory attributes of body lotions were evaluated using the numerical values of adjustable model parameters. This relatively cheap and fast approach exhibited a very good agreement with the results obtained by the sensory panel.